ANALISIS SISTEM PENYELENGGARAAN REKAM MEDIS DI RUMAH SAKIT NASIONAL GUIDO VALADARES, DILI TIMOR-LESTE - L. Pinto I, Inggrid Yolanda; Listyowati, Rina (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 3 (2022): Desember 2022DO - 10.24843/ACH.2022.v09.i03.p01, 2022)
ABSTRACT Medical records are information both written and recorded regarding identity, history taking, physical examination, laboratory, diagnosis, and treatment and medical actions given to patients. Hospital National Guido Valadares (HNGV) is the largest referral and education general hospital in Timor-Leste, this study aims to describe the medical record management system at HNGV. Descriptive research design with qualitative methods. Selection of informants using purposive sampling technique, data collection instruments using in-depth interview guidelines. The data were analyzed by content analysis method which consisted of data reduction steps, data presentation, and conclusion drawing. The results showed that the input aspect, the hospital already had SOPs and implementation guidelines, human resources and hospital funds were still limited. Aspects of the process, coding of medical actions and retention have not been carried out. Aspects of output, completeness of medical records has reached 80% and the implementation of medical records in hospitals is in accordance with existing SOPs. The conclusion from this research is that the hospital already has SOPs and implementation guidelines, the hospital's human resources and funds are not sufficient, the storage area for RM is still lacking. Suggestions for hospitals are to increase with additional human resources, make a priority list for the needs of each department, provide training on SOP socialization and implementation guidelines for the workforce. Keywords : Hospital, Medical Records, Assembling, Coding, Indexing, Filing.